2014
DOI: 10.1007/s00894-014-2098-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interaction of PCB180 to human serum albumin: insights from spectroscopic and molecular modelling studies

Abstract: Polychlorinated biphenyls (PCBs) are potentially hazardous to the environment because of their chemical stability and biological toxicity. In this study, we identified the binding mode of a representative PCB180 to human serum albumin (HSA) using fluorescence and molecular dynamics (MD) simulation methods. PCB180 bound exactly at subdomain IIIA of HSA based on the fluorescence study along with site marker displacement experiments. PCB180 also induced conformational changes that were governed mainly by hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…47 Ligand-bound crystal structures for the 66.5kDa protein show the various drug-, fatty acid-, ion-, and heme-binding sites of HSA, 48 and many methods have been employed to determine binding parameters. 41, 4951 In our present studies, we have measured the displacement of site-selective fluorescent probes from the two major drug-binding sites on HSA (i.e., Site I and Site II) as described by Sudlow et al 40 In this examination of LC-PCBs and their hydroxylated and sulfated metabolites, the displacement of: 5-dimethylamino-1-naphthalenesulfonamide (DNSA) for Site I and dansyl L-proline (DP) for Site II, shown in Figure 1, was used. 40 The displacement of these probes from their respective binding sites has been used to determine site-selectivity for ligands as well as to provide relative estimates of their binding affinities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Ligand-bound crystal structures for the 66.5kDa protein show the various drug-, fatty acid-, ion-, and heme-binding sites of HSA, 48 and many methods have been employed to determine binding parameters. 41, 4951 In our present studies, we have measured the displacement of site-selective fluorescent probes from the two major drug-binding sites on HSA (i.e., Site I and Site II) as described by Sudlow et al 40 In this examination of LC-PCBs and their hydroxylated and sulfated metabolites, the displacement of: 5-dimethylamino-1-naphthalenesulfonamide (DNSA) for Site I and dansyl L-proline (DP) for Site II, shown in Figure 1, was used. 40 The displacement of these probes from their respective binding sites has been used to determine site-selectivity for ligands as well as to provide relative estimates of their binding affinities.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the binding of individual higher chlorinated PCB congeners to HSA found that binding occurred at Site II. 49, 50 The binding of PCB 153 and the PCB 180 to HSA was determined using a combination of intrinsic fluorescence, probe displacement and molecular modelling. It was determined that both compounds bound to a single site of HSA, Sudlow Site II, and that binding was dominated by hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these few studies, however, are sometimes contradictory. [163][164][165] Neurotoxic effects of PCB exposure…”
Section: Human Serum Albumin (Hsa)mentioning
confidence: 99%
“…Previous studies on the binding of individual PCB congeners to HSA found that binding occurred at Site II. 163,165 One study, however, determined that binding occurred at Site I. 164 These seemingly contradictory conclusions stem from the differences in the studies.…”
Section: Recovery Of Pcb Sulfates Following Incubation With Hsamentioning
confidence: 99%